Small cell carcinoma with neuroendocrine differentiation of subglottic larynx- a case report - Becht, Rafał; Kiełbowski, Kajetan; Żychowska, Justyna; Dembowska, Wiktoria; Król, Małgorzata; Birkenfeld, Bożena; Owsiak, Mateusz; Lewandowska, Magdalena; Kubrak, Jadwiga; Amernik, Katarzyna (Frontiers in Oncology, 2023)
Small cell cancer (SCC) is a neuroendocrine neoplasm, which is most frequently found in the lungs. Extrapulmonary location of SCC is rare and may involve 2.5-5% of SCCs. We present a case of a 31-year-old male patient with an extremely uncommon subglottic SCC. The patient was qualified for a radical sequential chemoradiotherapy. After treatment, patient’s condition suggested complete remission. Recurrence was detected one year later, and the disease rapidly progressed, despite a second line chemotherapy. The patient died 29 months after initial diagnosis. This case aims to raise awareness on the aggressive laryngeal SCC and its good response to first line chemotherapy composed of cisplatin and etoposide, followed by radiotherapy.